Teachers’ Strategies in Managing a Large Class in Teaching English at SMP Negeri 01 Tanjung Selor - Trimar Keristiana; Arbain Arbain; Rinda Fitriana (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
Classroom management is an important concern for every teacher in making effective setting classroom in schools holds students together and offers them opportunity to achieving their goals in learning process especially in large classes with to much numbers of students. This research applied qualitative research. The subject of this research were the teacher’s and students of SMP NEGERI 01 Tanjung Selor. The researcher conducted interview to collect the data. The researcher did some steps to analyze the data, namely; data condensation, data display, and conclusion drawing.The result of this research showed that teachers mostly organize students into group during lesson, walk around classroom to check students work, set particular seating arrangement, address misbehavior and using variety of teaching method such as discussion, group work and group project to make students active during class. In addition, students’ perception has significant relationship between teachers’ strategies and student’s performance in learning English. The finding also showed that teachers has positive strategies in managing their class and the students enjoyed the method used by teachers during English lesson.